2008
DOI: 10.1007/s12298-008-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

ATP synthesis catalyzed by a V-ATPase: an alternative pathway for energy conservation operating in plant vacuoles?

Abstract: The electrochemical H + gradient generated in tonoplast vesicles isolated from maize seeds was found to be able to drive the reversal of the catalytic cycle of both vacuolar H + -pumps (Façanha and de Meis, 1998). Here we describe the reversibility of the vacuolar V-type H + -ATPase (V-ATPase) even in the absence of the H + gradient in a water-Me 2 SO co-solvent mixture, resulting in net synthesis of [γ-32 P]ATP from [ 32 P]P i and ADP. The water-Me 2 SO (5 to 20 %) media promoted inhibition of both PP i hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In eukaryotic vacuoles the internal pH is usually controlled by V-ATPases that pump protons inward at the expense of ATP (Rea and Poole, 1993;Uyama and Michibata, 1993;Masayoshi, 2000;Nelson et al, 2000;Kane and Smardon, 2003;Seidel, 2009). Nevertheless, in plant vacuoles (Façanha and Okorokova-Façanha, 2008) and in the prokaryotic organism Thermus thermophilus (Toei et al, 2007) energy conservation by V-ATPases has been reported. In Gram-negative bacteria the ETC and PMF-coupled ATPases are associated with the cytoplasmic membrane.…”
Section: Comparison With Other Organismsmentioning
confidence: 99%
“…In eukaryotic vacuoles the internal pH is usually controlled by V-ATPases that pump protons inward at the expense of ATP (Rea and Poole, 1993;Uyama and Michibata, 1993;Masayoshi, 2000;Nelson et al, 2000;Kane and Smardon, 2003;Seidel, 2009). Nevertheless, in plant vacuoles (Façanha and Okorokova-Façanha, 2008) and in the prokaryotic organism Thermus thermophilus (Toei et al, 2007) energy conservation by V-ATPases has been reported. In Gram-negative bacteria the ETC and PMF-coupled ATPases are associated with the cytoplasmic membrane.…”
Section: Comparison With Other Organismsmentioning
confidence: 99%
“…A decrease in cytosolic pH further increases the affinity to ATP to counteract cytosolic acidification and the regulation pays attention to cytosolic and luminal pH; information on the pH might be transported to the other side of the membrane, possibly by protonation of proteins ( Davies et al, 1994 ; Rienmueller et al, 2012 ). For completeness, ATP-synthesis was observed on the V-ATPase of maize vacuoles in the presence of a Me 2 SO-containing medium, which decreases the K m for phosphate because of the altered solvation energy of phosphate, and this reaction was observed even in the absence of a proton gradient ( Façanha and Okorokova-Façanha, 2008 ). The authors suggest that this might also occur as an energy-conserving mechanism in dehydrating environments like, for instance, seed cells.…”
Section: Enzymatic Properties and Enzyme Regulationmentioning
confidence: 99%